Ethics in Psychotherapy and Counseling : a Practical Guide. - Pope, Kenneth S.; Vasquez, Melba J. T.; Wiley eBooks (Hoboken : John Wiley & Sons, 2010)
Praise for Ethics in Psychotherapy and Counseling, Fourth Edition. "A stunningly good book. ... If there is only one book you buy on ethics, this is the one."--David H. Barlow, PhD, ABPP, Professor of Psychology and Psychiatry, Boston University. "The Fourth Edition continues to be the gold standard. ... a must-read in every counseling/therapy training program. It is that good and valuable."--Derald Wing Sue, PhD, Professor of Psychology and Education, Teachers College, Columbia University. "A must-have for therapists at every step of their career from student to wis.
Appendix A American Psychological Association: Ethical Principles of Psychologists and Code of Conduct With the 2010 AmendmentsAppendix B Canadian Code of Ethics for Psychologists (3rd Ed.); Appendix C Ethics Codes and Practice Guidelines for Assessment, Therapy, Counseling, and Forensic Practice; References; About the Authors; Author Index; Subject Index; STUDY PACKAGE CONTINUING EDUCATION CREDIT INFORMATION.
Includes bibliographical references and indexes.
John Wiley and Sons
Keywords: Counseling psychologists -- Professional ethics; Psychotherapists -- Professional ethics; Counseling psychology -- Moral and ethical aspects; Psychotherapy -- Moral and ethical aspects; Counseling psychologist and client; Counseling -- ethics; Psychotherapy -- ethics; Ethics, Professional; Health Personnel -- ethics; Professional Misconduct; Professional-Patient Relations -- ethics; Philosophy; BUSINESS & ECONOMICS -- Business Ethics; Electronic books